More sense of self-discipline, less procrastination: the mediation of autonomous motivation - Tao, Su; Jing, Yuan (Frontiers in Psychology, 2023)
Procrastination is considered a result of failed self-regulation. However, could experiencing a sense of successful self-discipline help to boost motivation and reduce procrastination? To explore this question, two studies were conducted to investigate the relationship between the sense of self-discipline, autonomous motivation, and procrastination. Results showed that trait sense of self-discipline negatively predicted general procrastination (Study 1); self-discipline primed participants procrastinated less than the control group (Study 2); autonomous motivation mediated the relationship between sense of self-discipline and procrastination (Study 1 and Study 2). These findings suggest that cultivating a sense of self-discipline can have positive effects on both autonomous motivation and procrastination, and provide useful guidance for interventions aimed at reducing procrastination.